DEVELOPMENT OF INTEGRTED IPA INTERACTIVE TYPE E-MODULE BASED ON COMMUNITY TECNOLOGY SCIENCE ON PLANT STRUCTURE AND FUNCTION MATERIAL FOR JUNIOR HIGH SCHOOL STUDENT - Dio Hilman Hafif; Tuti Lestari (Universe, 2022)
This study aims to produce an interactive e-module type integrated based on community technology science (STM) on material structure and function of plants that are valid and practical. This type of research is development research using 4-D models, define, design, and develop. The research subjects were students of SMPN 06 Pariaman class VIII.1 in the January-June 2021 semester. The research object of interactive science e-module integrated type STM based on plant structure and function material. The results showed that the e-module developed met the very valid criteria in the didactic aspect of 90.28%, constructs 91.67%, and technicality 96.88%. The results of the practicality assessment by teachers and students obtained an average value of very practical, ease of use 93.17, efficiency of use 89.37%, attractiveness 95.83%, easy to interpret 93.44% and has an equivalent of 92.63% . It was concluded that the integrated type of STM-based interactive science e-module on plant structure and function material that has been developed is declared valid and practical, to be used in science learning.